The Dark Side of Leader Narcissism: The Relationship Between Leaders' Narcissistic Rivalry and Abusive Supervision - Iris K. Gauglitz; Birgit Schyns; Theresa Fehn; Astrid Schütz (Journal of Business Ethics, 2022)
Narcissists often attain leadership positions, but at the same time do not care for others and often engage in unethical behaviors. We therefore explored the role of leader narcissism as an antecedent of abusive supervision, a form of unethical leadership. We based our study on the narcissistic admiration and rivalry concept (NARC) and proposed a direct positive effect of leaders' narcissistic rivalry—the maladaptive narcissism dimension—on abusive supervision. In line with trait activation and threatened egotism theory, we also proposed a moderated mediation assuming that leaders high in narcissistic rivalry would be particularly prone to showing abusive supervision in reaction to followers' supervisor-directed deviance, as this form of follower behavior would threaten their self-esteem. We conducted a field study with leader–follower dyads (Study 1) and an experimental vignette study with leaders (Study 2). Leaders' narcissistic rivalry was positively related to abusive supervision (intentions) in both studies. This effect was independent of followers' supervisor-directed deviance and leaders' perceived self-esteem threat. We discuss our findings in light of the NARC, as well as threatened egotism theory, and offer directions for future research. Finally, we make practical recommendations for organizations.
Keywords: 300; Abusive supervision; Narcissism; Threatened egotism; Perceived self-esteem threat; Supervisor-directed deviance